(untitled) (Philologia, 2021)
During the 19th and early 20th centuries, the Arab Cultural Revolution known as al-Nahda brought about an intense work of translation into Arabic, and adaptation of the most representative works of some European authors. My contribution highlights the main stages in the development of modern Arab literature, starting with al-Nahda, the cultural Arab Renaissance of the late 19th century. It investigates the economical and political background that made possible the cultural transfer brought out by the Renaissance. It stresses the importance of the literary translations from different Western literatures, and the extent to which they influenced the literatures in the Arab countries.